TINJAUAN YURIDIS BEA METERAI TERHADAP KEABSAHAN DOKUMEN MENURUT UNDANG-UNDANG NOMOR 10 TAHUN 2020 TENTANG BEA METERAI - Farhani Warta Pani; Eka Priambodo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the legal position of stamp duty on the validity of agreement documents within the Indonesian legal system, particularly based on Law Number 10 of 2020 on Stamp Duty. The primary focus is to examine whether the affixing of stamp duty affects the validity of an agreement and to what extent it plays a role in the evidentiary process in court. This research employs a normative juridical approach with a descriptive-analytical method that reviews statutory regulations, legal doctrines, and court decisions. The findings indicate that stamp duty is not a requirement for the validity of an agreement as stipulated in Article 1320 of the Indonesian Civil Code, but rather an administrative requirement that influences the evidentiary strength of documents in legal proceedings. Agreement documents without stamp duty remain legally valid in civil law but are only considered as preliminary written evidence unless stamp duty is subsequently affixed (nazegelen). Therefore, stamp duty plays a significant role in ensuring the formal legality and effectiveness of documents in legal processes.